The role of artificial intelligence in improving the efficiency of electronic administration and the development of public services - Mandour, Ahmed Mustafa Mamdouh (Journal of Legal and Political Studies, 2025)
This research deals with the role of artificial intelligence in enhancing the efficiency of electronic administration and the development of public services, in light of the digital transformations witnessed by governments and public institutions, and the research aims to study how to apply artificial intelligence techniques in improving public administration processes, through data analysis, and decision-making based on accurate information, and the research also discusses the role of artificial intelligence in improving public services, such as education, health, transportation, and social services, in addition to studying the impact of these technologies in enhancing transparency, reducing Bureaucracy, facilitating access to services. The research also reviews the challenges that may face the application of artificial intelligence in electronic governance, including issues related to cyber-security, protection of personal data, and legal issues related to regulation and control. In conclusion, the research shows how artificial intelligence can be a key driver for achieving effective e-governance, and how to employ it to ensure the provision of high-quality public services that meet the needs of citizens and contribute to achieving sustainable development. Keywords: artificial intelligence, public services, e-management, digital transformation, administrative efficiency.
Keywords: artificial intelligence; public services; emanagement; digital transformation; administrative efficiency